Household Saving Behavior on Formal Financial Institutions in Urban and Rural Areas - Muhammad Maftuhin; Deni Kusumawardani (Universitas Muhammadiyah Ponorogo, 2022)
This research aimed to examine the household saving behavior on formal financial institutions in urban and rural areas. The data sources of this research from the Central Bureau of Statistics (BPS), namely the 2018 Indonesia national socio-economic survey (SUSENAS) and the 2018 Indonesia village potential survey (PODES).The research sampleswere 126 539 households in urban and 168 562 households in rural spread over 34 provinces in Indonesia. The analytical method used logistic regression to determine the household behavior in the savings ownership in a formal bank institution.Several factors that affect savings ownership included socio-demographic and institutional factors. The estimation results showed that all socio-demographic factors affected savings ownership in urban, while institutional factors, namely government bank and private banks did not have a significant effect. Otherwise, institutional factors had a significant effect on savings ownership in rural, while socio-demographic factors (house ownership) did not havea significant effect. The findings were very important to improve saving behavior and provide alternative policies related to banking infrastructure development in Indonesia.